Burnout dan Persekutuan dalam Membangun Kualitas Pelayanan Tim Ibadah - Mailina Mailina; Wahyu Wijati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study is motivated by the increasing phenomenon of burnout among worship team members, which negatively affects the quality of church ministry. This study aims to: (1) analyze burnout in worship ministry, (2) examine the integration of psychological and theological perspectives through the concept of fellowship (koinonia), and (3) identify the role of fellowship in improving ministry quality. This research employs a qualitative approach using a literature review method based on relevant books and scholarly journals. The findings indicate that burnout is a multidimensional phenomenon influenced by ministry demands, weak community relationships, and insufficient spiritual depth. The integration of psychological and theological perspectives reveals that fellowship functions as a recovery mechanism that reduces burnout and enhances service quality. Healthy fellowship strengthens team cohesion, communication, and ministry motivation. In conclusion, the quality of worship ministry can only be developed through the integration of psychological well-being, strong community relationships, and deep spiritual formation.